Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1016/s0370-2693(99)00011-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive production of Drell–Yan pairs and heavy flavors

Abstract: Partonic interpretation of high-energy reactions is known to depend on a reference frame. Particularly, in the rest frame of the target Drell-Yan process looks like a freeing of the projectile ll fluctuation, rather than qq → ll annihilation. The lightcone representation for Drell-Yan reaction is very similar to that in DIS and exposes a substantial contamination of soft interactions which turns out to be dominant in diffractive production of lepton pairs and in nuclear shadowing. We estimate the fraction of d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 15 publications
(28 reference statements)
3
18
0
Order By: Relevance
“…By resumming higher twist terms we obtained an answer which is effectively leading twist. This result agrees with the previous predictions of [11,21]. Eq.…”
Section: Diffractive Structure Functionsupporting
confidence: 93%
See 1 more Smart Citation
“…By resumming higher twist terms we obtained an answer which is effectively leading twist. This result agrees with the previous predictions of [11,21]. Eq.…”
Section: Diffractive Structure Functionsupporting
confidence: 93%
“…That way we prove that due to the multiple rescattering effects diffraction becomes a leading twist effect [11], in the sense that diffractive structure function is not suppressed by extra powers of Q 2 with respect to the total structure function. At large enough Q 2 diffractive structure function should depend on center of mass energy for deep inelastic scattering, or, equivalently, on Bjorken x Bj , in the same way as the structure function F 2 .…”
Section: Introductionmentioning
confidence: 53%
“…It is shown that no radiation occurs without transverse momentum transfer to the quark (in contrast to gluon radiation). Therefore, the cross section for diffractive production of Drell-Yan pairs is suppressed compared to the expectation of [20] which is also based on an improper application of Eq. (A.6) to an exclusive channel.…”
Section: Introductionmentioning
confidence: 98%
“…Note that the q −q interaction emerges in (18)- (19) through the parameter λ defined in (20). In the limit λ → 0 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These distribution are flat in x ( e −y in rapidity ) for a single collision as observed at SPS energies. Already an analysis of the ISR data in pp collisions [2,3], and later data from HERA that shows a non-zero baryon asymmetry of ≈ 8% in γp reaction at more than 7 units of rapidity from the incident baryon [4] has demonstrated that additional mechanisms with a slower x and …”
mentioning
confidence: 99%